2016
DOI: 10.1186/s12889-016-3435-9
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall variation and child health: effect of rainfall on diarrhea among under 5 children in Rwanda, 2010

Abstract: BackgroundDiarrhea among children under 5 years of age has long been a major public health concern. Previous studies have suggested an association between rainfall and diarrhea. Here, we examined the association between Rwandan rainfall patterns and childhood diarrhea and the impact of household sanitation variables on this relationship.MethodsWe derived a series of rain-related variables in Rwanda based on daily rainfall measurements and hydrological models built from daily precipitation measurements collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 16 publications
2
29
0
2
Order By: Relevance
“…In order to control for the potential impact of precipitation on water quality and diarrhoea Levy et al, 2016;Mukabutera et al, 2016), total precipitation within the previous 10 days to each household's survey date was included in analyses as a potential confounder (Ercumen et al, 2015b). Data were downloaded in Network Common Data Format (NetCDF) for each village centroid from Climate Hazards Group InfraRed Precipitation with Station data 2.0 (CHIRPS) (Funk et al, 2015), which comprises daily gridded precipitation data derived from satellite and in-situ station data at 0.05 degree spatial resolution (approximately 5.3km).…”
Section: Precipitation Datamentioning
confidence: 99%
“…In order to control for the potential impact of precipitation on water quality and diarrhoea Levy et al, 2016;Mukabutera et al, 2016), total precipitation within the previous 10 days to each household's survey date was included in analyses as a potential confounder (Ercumen et al, 2015b). Data were downloaded in Network Common Data Format (NetCDF) for each village centroid from Climate Hazards Group InfraRed Precipitation with Station data 2.0 (CHIRPS) (Funk et al, 2015), which comprises daily gridded precipitation data derived from satellite and in-situ station data at 0.05 degree spatial resolution (approximately 5.3km).…”
Section: Precipitation Datamentioning
confidence: 99%
“…Our preliminary results showed that the point prevalence of ARI, diarrhoea, fever, stunting, underweight and wasting was reduced by an additional 12.6%, 6.2%, 12.4% 5.9%, 6.7% and 1.0%, respectively in the PIH‐supported areas compared to other rural areas (unpublished results). In another analysis, we found that rainfall‐related factors were also associated with these outcomes , and mechanisms for weather to impact these child health outcomes include crop production, water availability and quality, mosquito populations, bacteria and parasite growth, air quality and flooding . Finally, there is evidence that rainfall‐related factors vary between PIH‐supported areas and other areas of Rwanda (Figure ).…”
Section: Introductionmentioning
confidence: 84%
“…Although many such contextual factors may vary across geographical regions, we chose to examine the impact of rainfall which is well known to affect the incidence of some common infectious diseases and to vary in intensity and duration in different regions over time. Rainfall is unlike political or cultural factors that may affect the health of an area in that it is consistently and relatively accurately measured, and that rainfall patterns are extremely unlikely to vary based on the intervention and so are unlikely to be an intermediate on the causal pathway between the intervention and the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Another study from Ghana reported a negative relationship between diarrhoeal diseases and rainfall by analyzing routine data reported on childhood diarrhoea [29]. The findings of the research that employed secondary data of DHS in Rwanda found that higher runoff was protective of diarrhoea in children living household with unimproved toilet facilities [30]. The DHS 2014/2015 elucidated that only 11.6% of household used surface water and more than a half of households used improved latrines [31].…”
Section: Discussionmentioning
confidence: 99%